The Design of Promotional Media for "Pesta Wastra Indonesia" Komunitas Remaja Nusantara (KRN) in Jakarta - Muti Inaya; Ayoeningsih Dyah Woelandhary (IMAGIONARY, 2023)
Fabric tradition has been present since ancient times, but over time the use of fabrics in daily activities has shifted to formal fittings. Komunitas Remaja Nusantara (KRN) has activities to campaign for various types of fabrics / literature, especially for teenagers, under the name "Pesta Wastra Indonesia". Methods in design design and descriptive qualitative research are used to obtain precise and accurate data, so that the event design is in accordance with the target and the intended segment. The results of this design have a visual impact on increasing the amount of interest in teenagers to attend, because it is packaged with attractive visuals and in accordance with the teenage segment, as well as achieving the desired image, namely building the desire of teenagers to use fabrics in daily activities as a form of preservation of Indonesian cultural values.